A dominant avirulence gene in Orobanche cumana triggers Or5 resistance in sunflower. (20th June 2013) - Rodríguez‐Ojeda, M I; Pineda‐Martos, R; Alonso, L C; Fernández‐Escobar, J; Fernández‐Martínez, J M; Pérez‐Vich, B; Velasco, L
Summary: Orobanche cumana is a weed that grows as a root parasite on sunflower. In general, the O. cumana –sunflower parasitic system is regarded to follow the gene‐for‐gene model, although this has never been demonstrated at the genetic level in O. cumana . The Or5 dominant gene in sunflower confers resistance to O. cumana race E, but not to race F. The objective of this research was to study the inheritance of avirulence/virulence in crosses between plants of O. cumana lines classified as races E and F. Four race E and three race F lines were developed, from which four race E × race F cross‐combinations were made, in three cases including reciprocals. In all cases, F1 seeds did not have the ability to parasitise sunflower line P‐1380 carrying the Or5 gene, indicating dominance of race E avirulence allele(s). Five F2 populations comprising a total of 387 F2:3 families were evaluated on sunflower line P‐1380. In all cases, one‐fourth of the F2:3 families did not possess the ability to parasitise P‐1380 plants, suggesting that race E avirulence and race F virulence on P‐1380 are allelic and controlled by a single locus. This study demonstrated the gene‐for‐gene interaction in the O. cumana –sunflower parasite system and provided useful information to identify genes involved in O. cumana virulence. The approach followed in this research can contribute to define precisely races of the parasite on the basis of the presence of avirulence genes.